Analysis Strategic Partnership , Design Innovation Product Impact To Product Quality And Competitive Advantage SMES Convection In North Surabaya Area - Mohammad Fathur Rochman (NAROTAMA UNIVERSITY, Indonesia, 2019)
This research gives an overview of the studies emergence of the measurement influence to strateghic partnership, design innovation against product quality and competitiveness of small medium enterprises convection became object goal of my research. Type of this research is quantitative, population and sample based on the spread of to the 3 different companies with operations , designer and customer convection in the area North of Surabaya. Engineering data retrieval using the questionnaire. This research data analysis using the method of Partial least Squares (PLS) . Results the study proves all dependen variables a significant effect with a Quality Product (Y1) < 0.05, but the testing equation structure against a Competitive Advantage (Y2), design Innovation Product (X 2) showed no significant influence with p value 0.05 >. So, the competitive advantage in this region refer to the results of the product not of through an innovation concept with a uncertain results.